THE EFFECT OF COMPENSATION AND WORK ENVIRONMENT ON NON-ASN EMPLOYEE PERFORMANCE AT JEMBER GOVERNMENT: THE PATH ROLE OF JOB SATISFACTION - Ervan Setiawan; Sri Wahyu Lely Hana; Arnis Budi Susanto; Purnamie Titisari; NG Krishnabudi (Study Program of Management Faculty of Economics and Business University of Jember, 2022)
This study aims to determine the effect of compensation and work environment on performance through job satisfaction of non ASN employees of the Jember Regency Government. The population in this study was all non ASN employees of Jember Regency Government working period 2020. The sampling technique used was nonprobability sampling with a purposive sampling method that is the technique of determining the sample with certain considerations. The number of samples in this assessment was 52 respondents from the Regional Secretariat and all Agencies in the Jember Regency Government. This research uses primary data in the form of questionnaire. Data analysis method used in this study is the path analysis method. Based on the results of research and discussion shows that compensation influences job satisfaction, work environment has an effect on job satisfaction, compensation has an effect on performance, the work environment has an effect on performance, and the work environment has an effect on Job Satisfaction.